HUBUNGAN MASASE EFFLEURAGE TERHADAP NYERI AFTERPAIN PADA IBU NIFAS - Fulatul Anifah (Universitas Muhammadiyah Surabaya, 2022)
Objective: Uterine contractions occur physiologically and cause pain that can be bothersome to maternal comfort in the postpartum period. The most widely applied non-pharmacological techniques in dealing with pain in Indonesia are emotional support and massage. One of them is massage effleurage. This study aims to determine whether there is a relationship between effleurage massage and afterpain pain in postpartum women.Methods: This study uses a quasi-experimental design from November 2018 – April 2019 with 20 multiparous postpartum mothers as respondents determined by purposive sampling. Respondents filled out the consent form to become respondents during the study. Then the sample was divided into two groups: group intervention and control group. The instrument to assess the pain scale is the Numeric Rating Scale (NRS). Data analysis was carried out descriptively, and data normality test using Shapiro Wilk using the Mann-Whitney test to determine the difference in pain levels between the control and intervention groups using the Wilcoxon test and the effect of effleurage massage on pain reduction. The decrease in pain in the intervention group that was given effleurage massage occurred on the third day.Results: The results of the Mann-Whitney test in the intervention group, the value of sig.0.0001 (p<0.05), showed that the intervention group experienced a decrease in pain, so there was a significant difference between the control and intervention groups in reducing pain in multiparous postpartum mothers.Conclusion: In conclusion, effleurage massage’s effect reduces pain in multiparous postpartum mothers. There is a relationship between massage effleurage and afterpain pain in postpartum women. Postpartum mothers are expected to be able to carry out the effleurage massage technique independently to maintain comfort for themselves.